Z Generation Students and Their Digital Footprints - Karabatak, Songul; Karabatak, Murat (Institute of Electrical and Electronics Engineers Inc., 2020)
The purpose of this study is to evaluate the literature studies investigating the digital footprints of Generation Z students. For this purpose, studies in various databases related to the digital footprints of children, adolescents, and university students were evaluated in terms of analysis units of the publication type, research method, sampling, data collection tool, and results. However, it was seen that there were not many publications on this subject in the literature. Most of the studies examined were articles. In the studies, quantitative research methods were mostly used, therefore scales were preferred mostly. Also, it was observed that the ones who have the highest awareness about digital footprints are young people while the lowest are children. At the end of the study, various suggestions were made to increase the awareness of Generation Z students in digital footprints. © 2020 IEEE.
8th International Symposium on Digital Forensics and Security, ISDFS 2020 -- 1 June 2020 through 2 June 2020 -- Beirut -- 161222
Keywords: active digital footprints; digital footprints; Generation Z student; passive digital footprints